Special report of the General Superintendent of Common Schools of N.C. : made, according to law, to the governor, for the use of the General Assembly (Document (North Carolina. General Assembly), 1855)
1855 Special Report of the General Superintendent of the North Carolina Common Schools, C.H. Wiley, submitted to the General Assembly via Governor David S. Reid. The document consisted of an extensive review of the the history of education, teacher certification issues and other relevant information. An appendix contained a number of recommendations and requests for the improvement of teachers and education.